Hypoxia Inducible Factor 1: A Urinary Biomarker of Kidney Disease. Issue 3 (9th February 2017) - Movafagh, S; Raj, D; Sanaei‐Ardekani, M; Bhatia, D; Vo, K; Mahmoudieh, M; Rahman, R; Kim, EH; Harralson, AF
Abstract : Identifying noninvasive biomarkers of kidney disease is valuable for diagnostic and therapeutic purposes. Hypoxia inducible factor 1 (HIF‐1) expression is known to be elevated in the kidneys in several renal disease pathologies. We hypothesized that the urinary HIF‐1a mRNA level may be a suitable biomarker for expression of this protein in chronic kidney disease (CKD). We compared HIF‐1a mRNA levels from urine pellets of CKD and healthy subjects. To ensure that urinary HIF‐1a mRNA is of kidney origin, we examined colocalization of HIF‐1a mRNA with two kidney specific markers in urine cells. We found that HIF‐1a mRNA is readily quantifiable in urine pellets and its expression was significantly higher in CKD patients compared with healthy adults. We also showed that the urinary HIF‐1a mRNA comes primarily from cells of renal origin. Our data suggest that urinary HIF‐1a mRNA is a potential biomarker in CKD and can be noninvasively assessed in patients.